Pengembangan Instrumen Diagnostik Five-Tier Multirepresentasi untuk Mengidentifikasi Miskonsepsi Siswa pada Topik Gelombang - Tiara Sandari M; Maison, Maison; Ilham Falani (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Misconceptions on the topic of waves are a systemic problem in high school physics learning that requires a comprehensive diagnostic instrument. Conventional diagnostic instruments up to the four-tier generation have limitations in revealing the conceptual structure behind students' thinking errors. This study aims to develop a five-tier multi-representation diagnostic instrument on the topic of waves using the 4D model (Define, Design, Develop, Disseminate). The main innovation of this instrument lies in the integration of multi-representations (verbal, pictures, graphics, mathematical) in Tier 1 and the addition of a paraphrase tier (Tier 5) that asks students to rewrite their understanding in their own words. The development process includes needs analysis, designing a grid of 16 questions, validation by two experts, and a limited trial on 34 grade XI students of SMAN 13 Kota Jambi. The results of expert validation showed an average percentage of 91.25% (Very Good) from both validators. Content validity was met with a percentage of False Positive (FP) of 6.80% and False Negative (FN) of 4.41%, both below the 10% threshold. Construct validity was confirmed through a significant Product Moment correlation (r = 0.342–0.348; sig. < 0.05) and factor analysis with six significant factors (eigenvalue > 1). The instrument's reliability was high, with a Cronbach's Alpha of 0.726. This instrument is expected to help physics teachers diagnose students' misconceptions more precisely and thoroughly on the topic of waves.